Keabsahan Kontrak Bisnis Berbasis Contract Lifecycle Management Software - Amirah, Karina Adhania; Taupiqqurrahman, Taupiqqurrahman (Trunojoyo Madura University, 2023)
The development and adaptation of digitalization have exerted a significant influence various aspects of human life. In the realm of law, the impacts of digitalization can be observed through transformations contract formation. Contract Lifecycle Management Software emerged to facilitate the business contract processes for legal practitioners. However, by considering the various conveniences it offers, within its own sphere of application, such new technology can potentially give rise to legal issues. The legal research method in this research is normative juridical. The purpose of this research is conducted with the aim of examining the validity of utilizing Contract Lifecycle Management Software in simplifying the implementation of business contract processes in Indonesia, along with its concept of accountability for the potential occurrence of losses due to breach of contract. The research findings indicate that in its utilization, contracts formed through Contract Lifecycle Management Software can be deemed valid. However, it is necessary to draw the attention of the involved parties to continue adhering to the contract conditions stipulated within the applicable regulations. The responsibility for actions such as losses due to breach cannot be attributed to the technology itself, but rather directed towards its users due to arising errors or negligence.